Pengaruh Pengungkapan Emisi Karbon dan Leverage Terhadap Nilai Perusahaan - Putri Nur Cahyani; Juniati Gunawan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Rapid economic growth not only has a positive impact on people's living standards, but also damages natural resources and increases carbon emissions. The purpose of this study is to analyze the impact of disclosure of carbon emissions and leverage on firm value. The subjects of this research are manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. The sample in this study was 186 companies using purposive sampling method. The type of data in this study is secondary data in the form of annual reports and annual financial reports available on the Indonesia Stock Exchange website www.idx.co.id. The results showed that disclosure of carbon emissions has an effect on firm value, while leverage and firm size have no effect on firm value.